HUBUNGAN PERAN IBU DENGAN TINGKAT KEJADIAN SIBLING RIVALRY PADA ANAK USIA TODDLER (1-3 TAHUN) DI DESA SUMBERREJO PURWOSARI PASURUAN - Indatul Laili, Siti; Leli Agus Anika, Selvia (JURNAL KEPERAWATAN BINA SEHAT, 2014)
ABSTRACTSibling rivalry is the hostility and feelings of jealousy between siblings. Toddler age is the vital to child development, especially the development of emotions due to the egocentric that time was for the child. The vulnerable emotions in children ages toddler was jealous of taste. Jealousy going on aimed at getting attention. Less the maximum role of mother can lead to sibling rivalry in children. The purpose of this research is to analyze the role of the mothers relationship with a sibling rivalry the incidence rate in children aged toddler (1-3 years). Design of this research is analytic correlation with cross sectional approach. Samples taken with the Proportional Random Sampling technique as much as 62 respondents. In addition, questionnaire that has been checked its validity and reliability was used as the research instrument. Then the data are analyzed by using spearman rho correlation. The results showed that the mother in the village of Sumberrejo Purwosari Pasuruan most (45.2%) doing its part by category and have children who experienced sibling rivalry (61,3%) level. Statistical test results correlation Spearman Rank the value of p (0.000) < α (0.05). Conclusion of this research is the role of the mothers relationship is with the level of sibling rivalry instances on children aged toddler (1-3 years) in the village of Sumberrejo Purwosari, Pasuruan, therefore the role of the mother in educating children should correspond to the stages of growing flower child in the fulfillment of the basic needs of the child.Keywords: Role of the mother, Sibling Rivalry, Toddler